Проблемы и перспективы некоторых современных технологий термической конверсии твердых бытовых отходов - Васильев, И. В.; Капустенко, Пётр Алексеевич; Перевертайленко, Александр Юрьевич; Илюнин, О. О.; Бухкало, Светлана Ивановна; Арсеньева, Ольга Петровна (НТУ "ХПИ", 2013)
Проведено аналітичний огляд таких сучасних технологій термічної конверсії твердих побутових відходів, як високотемпературна інсінерація, піроліз, газифікація, включаючи плазмову газифікацію. Визначено переваги та недоліки технологій. Зазначено важливість інтеграції цих технологій з найкращими відомими технологіями з очистки синтез-газу, димових газів та води, що використовується.

The survey of some advanced thermal recycling tecnologies such as high-temperapture incineration, pyrolysis, gasification including plasma-aided gasification for municipal wastes conversion was carried out.The advantages and disadvantages of each technology are discussed. It was underlined on integration of mentioned above technologies with best available techniques of gas cleaning and water treatment.
Problems and perspectives of some advanced thermal recycling technologies of municipal wastes
Keywords: ТБО; плазменная инсинерация; плазменный термотрансформер; микроволновое излучение